Penerapan Metode JIGSAW untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas V SD Negeri 010 Beringin Jaya - Asriani, Eny (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
The author discussed the Indonesian language learning problem by incorporating the cooperative type jigsaw method in the teaching and learning process. The purpose of this study was to improve the learning outcomes of fifth-grade students at Beringin Jaya Elementary School using the jigsaw cooperative method. This research was conducted on the fifth-grade students of SDN 010 Beringin Jaya, with a total number of 20 students consisting of 12 female students and 8 male students. This research was conducted in 2 cycles starting from the end of March to May 2016. The results of the study showed that each cycle of teacher activity increased. It is seen that the teacher activity score in the first cycle got a score of 19 in the good category, and in the second cycle got a score of 23 categorized very well. Student activities from activities, in the first cycle, got a score of 20 categorized very well, and in the second cycle got a score of 22 very good categories. Additionally, the improvement of student learning outcomes was seen clearly, in the first cycle was 83.33%, while in the second cycle 91.66% of students completed. Thus, the use of the jigsaw cooperative method in Indonesian language learning can improve the learning outcomes of fifth-grade students of SDN 010 Beringin Jaya.